P140 EFFICACY AND SAFETY OF CHEMOTHERAPY CONTAINING NON–PEGYLATED LIPOSOMAL DOXORUBICIN IN PATIENTS AT HIGH CARDIOVASCULAR RISK: A SINGLE–CENTER EXPERIENCE. (18th May 2022) - Bisceglia, I; Camilli, M; Mistrulli, R; Cartoni, D; Matera, S; Canale, M; Battistini, R; Rigacci, L; Petrolati, S
Abstract: : Anthracyclines represent the most effective chemotherapeutic agent in the treatment of non–Hodgkin's lymphoma (NHL), although their use is limited due to the risk of cardiac toxicity. This occurs mainly in elderly patients, those with a history of cardiovascular (CV) disease and/or multiple concomitant risk factors. Liposomal doxorubicin has been shown to reduce this toxicity. The aim of this retrospective study is to investigate the use of non–pegylated liposomal doxorubicin in high–risk patients in terms of haematological response rate and CV events. In a single centre, 15 patients undergoing R–COMP regimen (Rituximab, Prednisone, Cyclophosphamide, Vincristine, Myocet liposomal doxorubicin) were consecutively collected from January 2020 to December 2021. The mean age of patients was 73.9 years and 60% were male. The baseline mean left ventricular ejection fraction (LVEF) was 55.9%; four patients had a baseline FE of < 50%, two of them had a severe reduction in LVEF. Among all patients, 86.7% had systemic hypertension, 40% diabetes mellitus, 46.7% dyslipidaemia and 20% a family history of CV disease. Moreover, 46.7% of patients had at least two concomitant risk factors and 20% at least three. 20% had a history of ischemic heart disease, 13.3% had previous exposure to anthracyclines and 20% with mediastinal radiotherapy; 26.7% had moderate to severe aortic valvulopathy. According to the joint Cardio–Oncology evaluation, 100% of patients had been considered unsuitable for conventional doxorubicin.. More than 85% of the cases were already on cardioactive therapy at baseline evaluation and 66.7% required titration or modification during chemotherapy. With R–COMP, the whole population was able to finish treatment achieved complete haematological remission. The mean LVEF at the end of treatment was 55.8% (p = 0.814). Conclusions: Our results support the efficacy and safety of R–COMP in a population at high risk for cardiac events, otherwise excluded from anthracycline–containing therapy. Liposomal formulatio reduces doxorubicin cardiomyocyte accumulation and thus toxicity, providing the best possible treatment for the majority of the onco–haematological population.